TAWHIDIC EPISTEMOLOGY AND UMMATIC MIND AS STRATEGIC RESOURCES IN ENHANCING SMALL BUSINESS RESILIENCE FOR UMMATIC EXCELLENCE - Mhd Sarif , Suhaimi; Abdul Razak , Dzuljastri; Ismail, Yusof (Online Journal of Islamic Management and Finance (OJIMF), 2025)
This study advances strategic management theory by integrating Islamic metaphysical constructs into the discourse on organizational resilience. Anchored in Tawhidic epistemology and the Ummatic mind, we explore taqwa (God-consciousness) as a faith-based intangible resource that shapes small business resilience. Drawing on the Resource-Based View (RBV), the study reconceptualizes resilience both as adaptive capacity and as an expression of spiritual and moral coherence. Utilizing a qualitative, interpretive case study approach involving five Malaysian small business owners, the study identified how internalizing taqwa through the Ummatic mind enhances ethical decision-making, stakeholder trust, and long-term strategic orientation. The findings demonstrate that the integration of Islamic metaphysical resources can produce sustained competitive advantage and lead to Ummatic excellence. This paper contributes to the emergent literature on spirituality in management and expanding the RBV by positioning metaphysical constructs as legitimate strategic assets.